A Review on Recent Trends of Sb2Se3 Thin Film Technology (International Journal of Scientific Research in Science and Technology, 2025)
Antimony selenide (Sb2Se3) thin films have emerged as a promising material for energy applications due to their unique optoelectronic properties, including high absorption coefficients, a suitable bandgap (~1-1.5 eV), and a polycrystalline orthorhombic structure. The material's abundance, non-toxic nature, and compatibility with sustainable manufacturing methods have further elevated its significance in photovoltaic and optoelectronic devices. This review provides a comprehensive analysis of the material properties, focusing on structural, optical, and electrical characteristics, along with recent advancements in synthesis techniques such as chemical and physical deposition methods. The potential of Sb2Se3 thin films in solar cell applications is highlighted, where power conversion efficiencies have steadily improved through innovative device architectures and material optimization. Additionally, this review addresses key challenges, including carrier recombination and stability issues, while proposing future research directions to enhance the performance and commercial viability of Sb2Se3-based devices. By consolidating existing knowledge, this study aims to serve as a foundation for advancing Sb2Se3 thin-film technologies.
Keywords: Energy; Solar; thin films